Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1977
DOI: 10.1002/app.1977.070210608
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cotton fiber maturity. III. A study of breaking load distribution of single fibers

Abstract: SynopsisBreaking load frequency distributions have been obtained at different test gauge lengths for several raw cottons differing in fiber cell wall maturity. The curve-fitting procedure for the analysis of the shape of observed breaking load histograms is described. The procedure yields several important parameters characterizing the raw cotton, such as the mean, mode, skewness, standard deviation, and the C.V. of breaking load. It is found that for all raw cottons, the observed breaking load distributions h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1979
1979
1997
1997

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…[ 14] (Figure 1 ). To perform these calibrations, two additional assumptions were needed: First, each fiber was assumed to exhibit linear load-elongation response from the displacement point where all crimp has been removed until it failed.…”
Section: Theoretical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 14] (Figure 1 ). To perform these calibrations, two additional assumptions were needed: First, each fiber was assumed to exhibit linear load-elongation response from the displacement point where all crimp has been removed until it failed.…”
Section: Theoretical Resultsmentioning
confidence: 99%
“…They reported that single fiber strength is significantly higher for long fibers than for short fibers sel8cted from the same cotton sample. More recently, Somashekhar et al [ 14] observed that single fiber breaking load histograms have a positive skew and are reasonably well represented by beta-type statistical distributions. They also reported that more immature cottons contain larger populations of weak fibers.…”
Section: How Sampling Affects Tenacitymentioning
confidence: 99%